Me trama: tu historia (2023)
Reading has become an obligation rather than a necessity, as Pablo Francisco Mora Venegas points out in his article "La motivación hacia la lectura de textos literarios" (Motivation towards reading literary texts). It has become a mechanical process that does not promote true reflection and interpretation of what is read. This turns reading comprehension into a mere requirement to pass a subject, leaving aside the achievement of educational objectives related to the acquisition of disciplinary content and the development of cognitive skills.